PERAN BPD (BADAN PERMUSYAWARATAN DESA) DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI DESA REMBUN, KECAMATAN SIWALAN, KABUPATEN PEKALONGAN PERIODE 2008-2014 - Risala, Fahmi (Journal of Politic and Government Studies, 2013)
ABSTRACTBPD (Village Consultative Board) has given hope for the future of the village. The existence of BPD as parliamentary institution of village is expected to carry out the duties and functions as the channeling of people aspirations makes village regulation along with village heads and supervisy village governance. It is the basis of the concept of democracy based on government from the people, by the people and for the people. In this case, the BPD has a very important role. This study aims to find the reasons why the BPD Rembun Village didn’t play its role optimally and identify factors that hinder the role of BPD in implementation of the village governance.The place this research is Rembun Village, Subdistrict Siwalan, Pekalongan District. The study is limited to the period 2008-2014. The research informants are member of BPD Rembun Village, village government officials, and village community leaders that purposively selected. The data obtained in the form of primary data and secondary data. Researcher used interviews to collect data, then analyzed through the data collection, data reduction, data display and the last stage are conclusion or verification.The results of this study describe that the role of the Village Rembun BPD have not be able optimally in implementation of the village governance. The first, the representative function of members of BPD Rembun village are passive. Second, in the supervision function, BPD ignore his duties because more busy with work outside. Third, the legislative function of BPD is less initiative and less active in filing and making Perdes (village regulations).Keywords: Implementation of the village governance, BPD (Village Consultative Board).* Mahasiswa